Calidad de vida en población desplazada por el conflicto interno en Colombia - German Darío Vallejo Bravo (Les Cahiers ALHIM)
This article analyzes one of the main consequences of internal armed conflict in Colombia which is the forced displacement, the victims who suffer it and its influence on their quality of life. For this purpose, a review of the social situation and violence in Colombia is carried outdiscussing the theoretical term quality of life, exposing, as well, some scientific input to contextualize the problem at hand. Finally, a critic look at the state of quality of life in the displaced in Colombia is presented.